Kul’tavyja kamjani Belarusi The Cult Stones in Belarus - Ljavkov, Ernst; Karabanav, Aljaksandr; Dučyc, Ljudmila; Zajkovski, Edvard; Vinakurav, Valeryj (Studia mythologica Slavica, 2015)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The article analyses cult stones on the territory of Belarus, among them such types as stones with footprints, stones for protection, officinal- and treasure-stones, petrified people and animals. The stones are known under the following names: the God’s footprint, the Holy stone, Volas, Dazhdzboh (Rain-God), Kapavishcha (Sanctuary), Forefather, and others. Even today people make sacrifice (money, flowers, apples) to many of these stones.